Digital twins and shifts in the relationship between health and disease Digitale Zwillinge und Verschiebungen im Verhältnis von Gesundheit und Krankheit - Braun, Matthias (Zeitschrift für medizinische Ethik, 2022)
In this article, I explore the question of what shifts are emerging in the relationship between health and disease through new AI-based prediction systems. One example of such prediction systems are digital twins for predicting changes in parts of a person's physical body. In a first step, I discuss possible fundamental determinations of the relationship between health and disease. In a second step, I examine from a theological and philosophical perspective what it means when a digital twin simulates and predicts states of illness vicariously. In a concluding third step, I draw a line to the debates about freedom to illness and show how these debates can help us to think about a responsible approach to digital twins.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Digital twins; disease; health; illness; predictive medicine; right not to know; sickness